"No Fracking Way" vs. "Drill Baby Drill": A Restructuring of Who Is Pitted Against Whom in the Narrative Policy Framework. Issue 4 (17th October 2018) - Gottlieb, Madeline; Bertone Oehninger, Ernst; Arnold, Gwen
Abstract : Narratives are highly consequential in policy processes because they shape public perception of policy issues. The Narrative Policy Framework (NPF) seeks to predict the extent to which narratives are strategically used to influence policy outcomes. Its core hypotheses center around a winning vs. losing dichotomy, in which winning and losing narratives employ distinct sets of strategies. Due to the newness of the theory, there are few empirical tests of its components, and their results are inconclusive. We posit that the winning–losing paradigm does not accurately predict narrative strategy use. To test this hypothesis, we examine a policy dilemma where contextually similar jurisdictions adopted multiple different policy solutions over a common time period. From 2008 to 2012, more than 260 New York municipalities passed policies related to hydraulic fracturing (fracking). We analyze editorial content from two local newspapers in central New York whose distribution covers municipalities that adopted anti‐ and pro‐fracking policies. Our findings reveal that narrators consistently use narrative strategies that correspond to the side of the issue they support, regardless of whether they are winning or losing the policy debate. This suggests the NPF's winning–losing dichotomy may not be not well suited to predicting narrative strategy use or policy outcomes.